Gender Representation in Merdeka Curriculum ELT Textbooks: A Corpus-assisted Study - Siti Zulalina Adawiyah; Ikmi Nur Oktavianti (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
Gender representation in English textbooks has been an issue for a long period of time; it is important to monitor and assess the evolution of English textbooks regularly. This research examined how gender representation is presented in Merdeka curriculum-mandated English textbooks since there are gender imbalances and gender misconceptions in previous mandated English textbooks. Gender-related references used in the textbooks are analyzed using the Corpus tool and then measured to see how each gender is represented. Textbook analysis is important since they deliver values and could impact student’s perception of gender. This research intended to examine gender-related references and characteristics, therefore, corpus tools such as KWIC, plot, cluster, word, and collocate are used. This research found five categories of gender-related references in these textbooks: famous names, fictional names, ordinary names, generic nouns, and pronouns. Moreover, it is found that the Merdeka curriculum English textbooks did not present equal gender representation where male references are underrepresented and portrayed to only possess two emotions, happy and sad. Yet, female references dominated the presentation and portrayed as independent individuals who experienced lots of emotions such as furious, falling in love, ashamed, and other emotional attributes. Hence, the imbalance representation in textbooks should be revisited and should be based on more various natures of human emotions and roles.